(untitled) (مجلة العلوم الشاملة, 2026)
This paper reviews the relationship between transformational leadership and employee job satisfaction, drawing on available theoretical and empirical literature. Transformational leadership is characterized by four main components: idealized influence (charisma), individualized consideration, intellectual stimulation, and inspirational motivation. Job satisfaction is defined as a positive emotional state resulting from an employee’s appraisal of their work and professional experiences. The review reveals a positive and statistically significant relationship between transformational leadership and employee satisfaction across various contexts, including higher education, healthcare, banking, hospitality, and non-profit organizations. Mediating mechanisms such as team effectiveness, empowerment, and organizational culture are also identified. The review concludes that transformational leadership enhances job satisfaction by meeting subordinates’ expectations, providing individual support, fostering creativity and innovation, and communicating a clear and compelling organizational vision.